Auxiliary circuit for zero‐voltage‐transition interleaved pulse‐width modulation buck converter. Issue 3 (1st March 2016) - Esteki, Morteza; Adib, Ehsan; Farzanehfard, Hosein; Arshadi, Sayed Abbas
Abstract : An interleaved zero‐voltage‐transition (ZVT) pulse‐width modulation (PWM) buck converter is proposed in this study. The proposed converter consists of two identical buck converters connected in parallel and an auxiliary circuit. The auxiliary circuit has only one active switch. Zero‐voltage switching condition for main switches and also, zero‐current switching condition for the auxiliary circuit semiconductor components are achieved. Principle of operation and analysis of the proposed converter is provided. Moreover, the extension of the proposed idea to interleaved buck–boost, interleaved flyback and interleaved forward converters are presented. A 160 W prototype of the proposed ZVT PWM buck converter is implemented and the results are presented to verify the validity of theoretical analysis.